Atmospheric microplastic deposition in an urban environment and an evaluation of transport. (March 2020) - Wright, S.L.; Ulke, J.; Font, A.; Chan, K.L.A.; Kelly, F.J.
Highlights: Microplastics were present in atmospheric deposition in central London. Comparing equal size classes, levels were 20 times greater than in a remote location. Fibrous morphologies dominated and polyacrylonitrile was the most common polymer. Local source areas influenced microplastic levels. Abstract: Microplastics are a global environmental issue contaminating aquatic and terrestrial environments. They have been reported in atmospheric deposition, and indoor and outdoor air, raising concern for public health due to the potential for exposure. Moreover, the atmosphere presents a new vehicle for microplastics to enter the wider environment, yet our knowledge of the quantities, characteristics and pathways of airborne microplastics is sparse. Here we show microplastics in atmospheric deposition in a major population centre, central London. Microplastics were found in all samples, with deposition rates ranging from 575 to 1008 microplastics/m 2 /d. They were found in various shapes, of which fibrous microplastics accounted for the great majority (92%). Across all samples, 15 different petrochemical-based polymers were identified. Bivariate polar plots indicated dependency on wind, with different source areas for fibrous and non-fibrous airborne microplastics. This is the first evidence of airborne microplastics in London and confirms the need to include airborne pathways when consolidating microplastic impacts on the wider environment and human health.